Nonlinear optimal control of electro-hydraulic actuators. (March 2021) - Rigatos, G.; Abbaszadeh, M.; Siano, P.; Cuccurullo, G.
Abstract: A nonlinear optimal (H-infinity) control approach is proposed for electro-hydraulic actuators. Control of electrohydraulic actuators is a non-trivial problem because of the nonlinearities and underactuation in their dynamics. The article's approach relies first on approximate linearization of the state–space model of the electrohydraulic actuator, according to first-order Taylor series expansion and the computation of the related Jacobian matrices. For the approximately linearized model of the actuator, a stabilizing H-infinity feedback controller is designed. To compute the controller's gains an algebraic Riccati equation is solved at each time-step of the control algorithm. The global stability properties of the control scheme are proven through Lyapunov analysis. The proposed control scheme retains the advantages of typical optimal control, that is fast and accurate tracking of the reference setpoints under moderate variations of the control inputs.